An iron-based Prussian blue positive electrode material and its preparation method and application

By using a water trapping agent and water in the preparation of iron Prussian blue positive electrode material, the problems of complex operation, high energy consumption and crystallization water in the prior art are solved, the ratio and circulation performance of the material are improved, the preparation process is simplified and the cost is reduced.

CN119774638AActive Publication Date: 2025-04-08INNER MONGOLIA MURRAY ENERGY MATERIALS CO LTD

Patent Information

Application Number
CN202510273560.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The existing preparation methods for iron-based Prussian blue materials are complex in operation, high energy consumption, and crystallization water is easily formed when co-precipitated in aqueous solution, affecting electrochemical performance.

Method used

The method of mixing ferrous salt, acid and water, cyanogen source, sodium replenishing agent and water, and mixing water trapping agent and water for aging is adopted to improve the solubility of salt substances, prevent water molecules from entering the gaps of the material, and simplify the operation process.

Benefits of technology

It significantly improves the rate performance and cycle performance of Prussian blue materials, simplifies the preparation process, reduces production costs, and is suitable for large-scale and rapid batch preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774638A_ABST
    Figure CN119774638A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and discloses an iron-based Prussian blue positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: mixing ferrous salt, acid and water to obtain a first solution; mixing a cyanide source, a sodium supplement and water to obtain a second solution; mixing a water scavenger and water to obtain a third solution; mixing the first solution, the second solution and the third solution, and aging to obtain an iron-based Prussian blue positive electrode material. The iron-based Prussian blue positive electrode material prepared by the method of the present invention has a high specific capacity, a high coulomb efficiency and a high capacity retention rate at a high rate, and exhibits good rate performance and cycle performance when used as a positive electrode material for a sodium ion battery, providing a broad application prospect for low-cost, high-performance sodium ion batteries in the field of large-scale energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an iron-based Prussian blue positive electrode material and a preparation method and application thereof. Background Art

[0002] As one of the advanced electrochemical energy storage systems, lithium-ion batteries are widely used in various portable electronic devices. However, lithium-ion batteries face serious problems such as shortage of lithium resources. Sodium and lithium are in the same family and have similar chemical properties. At the same time, sodium resources are abundant and widely distributed, so sodium-ion batteries are considered to be a powerful supplement to lithium-ion batteries. Among them, sodium positive electrode materials, as the key component of sodium-ion batteries, are the key factors affecting the energy density, power density and safety of sodium-ion batteries. Iron-based Prussian blue materials have become highly competitive and mass-producible positive electrode materials due to their open three-dimensional framework structure, large interstitial space and ion diffusion channels, as well as their low cost and simple synthesis steps.

[0003] At present, the common preparation of high crystallinity Prussian blue materials is mainly coprecipitation. However, when coprecipitating in aqueous solution, the reaction speed of metal salt and sodium ferrocyanide is very fast, causing water molecules to enter the gap position to form crystal water, thereby causing the electrochemical performance of Prussian blue positive electrode materials to decrease. In order to improve the crystal water problem, the commonly used method is to add a complexing agent to slow down the reaction speed of metal salt and sodium ferrocyanide and reduce the generation of defects. In addition, the coprecipitation reaction solution system can be regulated to reduce the crystal water entering the gap during the reaction, thereby improving the crystallinity of the Prussian blue material. For example, Chinese invention patent application CN119018911A performs a solvothermal reaction of a cobalt salt solution and a ferrocyanide salt solution in a mixed solution of water and an organic solvent. During the reaction, the organic solvent will be embedded in the crystal interior of the Prussian blue analog, replacing the water molecules in the original position, thereby reducing the water content. Another example is the Chinese invention patent application CN116605887A, which dissolves a cyanide source, a metal source, an antioxidant, and a complexing agent in a polar organic solvent, and uses microwave synthesis to rapidly synthesize the Prussian blue complex that could not occur in a non-aqueous solvent. Another example is the Chinese invention patent application CN116598484A, which uses a poorly soluble solvent of sodium ferrocyanide as a reaction solution system, and adjusts the solubility to control the reaction rate, thereby controlling the generation of defects during crystal growth. In summary, the currently disclosed methods for adjusting the solvent system are to directly dissolve the cyanide source, metal source, complexing agent, etc. in an organic solvent system for coprecipitation reaction. However, the organic solvent system has low solubility for the above-mentioned salt substances, resulting in stratification or salt precipitation during dissolution, and even causing the reaction system to present a solid-liquid two-phase, resulting in the reaction occurring only at the interface, which seriously affects the uniformity and product quality of the reaction solution system, and reduces the preparation efficiency. In order to increase the solubility of salt substances in organic solvent systems, the solvent heat or microwave heating used will increase the complexity of the operation and energy consumption, which is not conducive to large-scale rapid batch preparation. Summary of the invention

[0004] The purpose of the present invention is to provide an iron-based Prussian blue positive electrode material to solve the problems of complex operation and high energy consumption in the existing preparation methods of iron-based Prussian blue materials, while significantly improving the rate performance and cycle performance of Prussian blue materials.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing an iron-based Prussian blue positive electrode material, comprising the following steps: Mixing ferrous salt, acid and water to obtain a first solution; mixing a cyanide source, a sodium supplement and water to obtain a second solution; mixing the water-capturing agent with water to obtain a third solution; The first solution, the second solution and the third solution are mixed and aged to obtain an iron-based Prussian blue positive electrode material; The water-capturing agent is an acidic or neutral organic solvent having a functional group capable of forming hydrogen bonds and being miscible with water in any proportion; the functional group capable of forming hydrogen bonds should have both a hydrogen bond donor and a hydrogen bond acceptor.

[0006] Preferably, in the preparation method, the ferrous salt includes ferrous chloride or ferrous sulfate; In the first solution, the ratio of the molar amount of the ferrous salt to the volume of the water is 1 mmol: 3-7 mL.

[0007] Preferably, in the preparation method, the acid includes hydrochloric acid and / or acetic acid, and the mass concentration of the acid is 36-38%; In the first solution, the volume ratio of the acid to the water is 1:10-40.

[0008] Preferably, in the preparation method, the cyanide source includes sodium ferrocyanide; the sodium supplement includes one or more of sodium chloride, sodium acetate, and sodium oxalate; The molar ratio of the cyanide source to the sodium supplement is 1:2-8; In the second solution, the ratio of the molar amount of the cyanide source to the volume of the water is 1 mmol: 3-7 mL.

[0009] Preferably, in the preparation method, the water-capping agent includes one or more of methanol, formic acid, formamide, ethanol, acetic acid, ethylene glycol, propanol, propionic acid, propylene glycol, glycerol, and isopropanol; The concentration of the functional groups capable of forming hydrogen bonds in the water-capping agent in the third solution is 0.92-1.28 mol / L.

[0010] Preferably, in the preparation method, the molar ratio of the ferrous salt to the cyanide source is 1:0.5-2; The volume ratio of water in the first solution to the third solution is 1:2-6.

[0011] Preferably, in the preparation method, the first solution, the second solution and the third solution are mixed by simultaneously dropping the first solution and the second solution into the third solution for dispersion; The rate at which the first solution is added dropwise to the third solution is independently 0.5 to 5 mL / min and the temperature of the addition is room temperature; The dispersion time is 2 to 8 hours.

[0012] Preferably, in the preparation method, the aging temperature is room temperature, and the aging time is 8 to 48 hours.

[0013] The invention also provides an iron-based Prussian blue positive electrode material prepared by the preparation method.

[0014] The present invention also provides an application of the iron-based Prussian blue positive electrode material in a sodium ion battery.

[0015] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts a method of first dissolving salt substances such as iron source and cyanide source in water, and then mixing the two salt solutions in a third phase water-scavenging agent solution, thereby improving the solubility of the salt substances, preventing the problem of the salt substances being insoluble in the organic phase solution and stratifying and precipitating, simplifying the operation process, and improving the uniformity of subsequent reactions and the quality of products.

[0016] (2) The water scavenger used in the present invention interacts with water molecules through hydrogen bond donors (hydrogen atoms covalently bonded to atoms with high electronegativity, such as hydrogen atoms in hydroxyl or amine groups) and hydrogen bond acceptors (atoms with high electronegativity having lone pairs of electrons, such as oxygen atoms in carbonyl and hydroxyl groups) to form a bulk hydrogen bond network, thereby binding water molecules in the solution, reducing the movement and reactivity of free water molecules, increasing the viscosity of the solution, and inhibiting water molecules from entering the gaps of Prussian blue. In addition, the diffusion rate of the reactants in the solution is reduced, providing a certain degree of control over the growth direction of the crystal, thereby inducing orderly crystal growth and increasing the stability of the crystal, and reducing the defects of the iron-based Prussian blue crystal under the combined action of acid. Taking hydrochloric acid as an example, the H + Ions and water-scavenging agents work together to adjust the charge distribution in the solution. This adjustment affects the charge state on the surface of Prussian blue crystals, making the deposition of crystals more orderly. - It may exist on the crystal surface as a weakly adsorbed ion, further inhibiting disordered aggregation. At the same time, the loss of the water-scavenging agent is small, and it can be recycled, reducing costs and saving raw materials.

[0017] (3) In the solution of the present invention, a sodium supplement is also added. The sodium ions of the sodium supplement can fill the vacancy defects, stabilize the crystal framework structure of Prussian blue, and enhance the ion conductivity. At the same time, the high sodium ion concentration helps to inhibit the rapid precipitation of crystals and form more uniform and regular crystals. The present invention does not require the addition of a complexing agent, further simplifies the preparation process, and reduces the production cost.

[0018] (4) The iron-based Prussian blue positive electrode material prepared by the method of the present invention has high specific capacity, high coulombic efficiency and high capacity retention rate at high rate. When used as a positive electrode material for sodium ion batteries, it exhibits good rate performance and cycle performance, providing a bright prospect for the use of low-cost, high-performance sodium ion batteries in the field of large-scale energy storage.

[0019] (5) The synthesis method of the present invention selects sodium ferrocyanide, ferrous sulfate and a specific type and concentration of a water scavenger for co-precipitation in an aqueous phase, and strictly controls the ratio of the water scavenger and the synthesis time, thereby regulating the hydrogen bond density and the viscosity of the system, thereby ensuring the efficient dissolution of salts in the solvent system and limiting the embedding of water molecules in the gaps, thereby obtaining an iron-based Prussian blue positive electrode material with a low-defect crystal structure. The raw materials are simple and easy to obtain, the process operation is simple, the energy consumption is low, the experimental repeatability is good, and it is easy to industrialize production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0021] Figure 1 This is the XRD pattern of the iron-based Prussian blue positive electrode material of Example 1; Figure 2 This is a SEM image of the iron-based Prussian blue positive electrode material of Example 1; Figure 3 This is a SEM image of the iron-based Prussian blue positive electrode material of Comparative Example 1; Figure 4 The charge and discharge data of the sodium ion batteries of application examples 1-2 and comparative application examples 1-3 at a current of 10C for the first 500 cycles; Figure 5 The figure is a rate performance diagram of the sodium ion battery of application examples 1-2 and comparative application examples 1-3; Figure 6 The charge and discharge curves of the sodium ion battery of Application Example 1 during the first three cycles at a current of 0.1C. DETAILED DESCRIPTION

[0022] The present invention provides a method for preparing an iron-based Prussian blue positive electrode material, comprising the following steps: Mixing ferrous salt, acid and water to obtain a first solution; mixing a cyanide source, a sodium supplement and water to obtain a second solution; mixing the water-capturing agent with water to obtain a third solution; The first solution, the second solution and the third solution are mixed and aged to obtain an iron-based Prussian blue positive electrode material; The water-capturing agent is an acidic or neutral organic solvent having a functional group capable of forming hydrogen bonds and being miscible with water in any proportion; the functional group capable of forming hydrogen bonds should have both a hydrogen bond donor and a hydrogen bond acceptor.

[0023] In the present invention, the ferrous salt preferably includes ferrous chloride or ferrous sulfate, and more preferably ferrous sulfate.

[0024] In the present invention, in the first solution, the molar ratio of the ferrous salt to the volume of the water is preferably 1 mmol:3-7 mL, more preferably 1 mmol:4-6 mL, and more preferably 1 mmol:5 mL.

[0025] In the present invention, the acid preferably includes hydrochloric acid and / or acetic acid, and more preferably hydrochloric acid.

[0026] In the present invention, the mass concentration of the acid is preferably 36-38%, more preferably 36-37%, and more preferably 36%.

[0027] In the present invention, in the first solution, the volume ratio of the acid to the water is preferably 1:10-40, more preferably 1:20-30, and more preferably 1:25.

[0028] In the present invention, the cyanide source preferably includes sodium ferrocyanide.

[0029] In the present invention, in the second solution, the molar ratio of the cyanide source to the volume of the water is preferably 1 mmol:3-7 mL, more preferably 1 mmol:4-6 mL, and even more preferably 1 mmol:5 mL.

[0030] In the present invention, the sodium supplement preferably includes one or more of sodium chloride, sodium acetate, and sodium oxalate, and further preferably includes sodium chloride, sodium acetate, or sodium oxalate, and more preferably sodium chloride.

[0031] In the present invention, the molar ratio of the cyanide source to the sodium supplement is preferably 1:2-8, more preferably 1:3-6, and more preferably 1:5-5.2.

[0032] In the present invention, the functional group capable of forming a hydrogen bond preferably includes one or more of a hydroxyl group, an amide group and a carboxyl group, more preferably includes a hydroxyl group and / or a carboxyl group, and more preferably is a hydroxyl group.

[0033] In the present invention, the water-capping agent preferably includes one or more of methanol, formic acid, formamide, ethanol, acetic acid, ethylene glycol, propanol, propionic acid, propylene glycol, glycerol, and isopropanol, and further preferably includes ethylene glycol, propylene glycol or glycerol, and more preferably ethylene glycol.

[0034] In the present invention, the concentration of the functional groups capable of forming hydrogen bonds in the water-scavenging agent in the third solution is preferably 0.92-1.28 mol / L, more preferably 1-1.2 mol / L, and more preferably 1.1 mol / L.

[0035] In the present invention, the molar ratio of the ferrous salt to the cyanide source is preferably 1:0.5-2, more preferably 1:0.5-1.5, and more preferably 1:1.

[0036] In the present invention, the volume ratio of water in the first solution to the third solution is preferably 1:2-6, more preferably 1:3-5, and even more preferably 1:4.

[0037] In the present invention, the method of mixing the first solution, the second solution and the third solution is preferably: the first solution and the second solution are simultaneously dropped into the third solution for dispersion.

[0038] In the present invention, the rate at which the first solution is added dropwise to the third solution is independently preferably 0.5 to 5 mL / min, more preferably 0.5 to 2 mL / min, and even more preferably 1 mL / min.

[0039] In the present invention, the dropping temperature is preferably room temperature.

[0040] In the present invention, the dispersion time is preferably 2 to 8 hours, more preferably 4 to 6 hours, and even more preferably 5 hours.

[0041] In the present invention, the aging temperature is preferably room temperature.

[0042] In the present invention, the aging time is preferably 8 to 48 hours, more preferably 16 to 36 hours, and more preferably 24 hours.

[0043] In the present invention, the aging preferably further comprises: centrifugal washing and vacuum drying in sequence.

[0044] In the present invention, the centrifugal washing reagent is preferably water.

[0045] In the present invention, the centrifugal speed of the centrifugal washing is preferably 3000-6000 rpm, more preferably 3500-4500 rpm, and more preferably 4000 rpm.

[0046] In the present invention, the number of centrifugal washing is preferably 2 to 5 times, more preferably 3 to 4 times, and more preferably 3 times.

[0047] In the present invention, the vacuum drying temperature is preferably 80-120°C, more preferably 100-120°C, and even more preferably 110°C.

[0048] In the present invention, the vacuum drying time is preferably 8 to 24 hours, more preferably 10 to 18 hours, and more preferably 12 hours.

[0049] The invention also provides an iron-based Prussian blue positive electrode material prepared by the preparation method.

[0050] The present invention also provides an application of the iron-based Prussian blue positive electrode material in a sodium ion battery.

[0051] In the present invention, the application method is not limited, and any method known to those skilled in the art may be used.

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] In the embodiments and comparative examples of the present invention, ferrous sulfate is ferrous sulfate heptahydrate (FeSO4·7H2O), ferrous chloride is FeCl2, sodium ferrocyanide is Na4Fe(CN)6, and sodium chloride is NaCl.

[0054] Example 1

[0055] This embodiment provides a method for preparing an iron-based Prussian blue positive electrode material, comprising the following steps: Dissolve 5 mmol of FeSO4·7H2O and 1 mL of concentrated hydrochloric acid (mass concentration 36%) in 25 mL of deionized water and stir evenly to obtain a first solution; Dissolve 5 mmol of Na4Fe(CN)6 (mass 1.52 g) and 1.5 g of NaCl (molar weight 25.67 mmol) in 25 mL of deionized water and stir well to obtain a second solution; 100 mL of 0.55 mol / L ethylene glycol-water solution was used as the third solution, wherein the molar concentration of hydroxyl group was 1.10 mol / L; Under stirring conditions at room temperature, the first solution and the second solution were simultaneously added to the third solution through a peristaltic pump at a speed of 1 mL / min. After the addition was completed, the solution became a blue suspension; stirring was continued for 5 hours, and finally aged at room temperature for 24 hours; after pouring out the supernatant, the obtained blue precipitate was washed three times by centrifugation with deionized water at a centrifugal speed of 4000 rpm, and then vacuum dried at 110°C for 12 hours to obtain an iron-based Prussian blue positive electrode material, recorded as EG-PBA.

[0056] Example 2

[0057] Dissolve 5 mmol of FeSO4·7H2O and 1 mL of concentrated hydrochloric acid (mass concentration 36%) in 25 mL of deionized water and stir evenly to obtain a first solution; Dissolve 5 mmol of Na4Fe(CN)6 (mass 1.52 g) and 1.5 g of NaCl (25.67 mmol) in 25 mL of deionized water and stir well to obtain a second solution; 100 mL of a 0.37 mol / L glycerol-water solution was used as the third solution, wherein the molar concentration of hydroxyl groups was 1.10 mol / L; Under stirring at room temperature, the first solution and the second solution were simultaneously added to the third solution at a speed of 1 mL / min through a peristaltic pump, and the solution became a blue suspension after the addition was completed; stirring was continued for 5 hours, and finally aged at room temperature for 24 hours; after pouring out the supernatant, the obtained blue precipitate was washed three times by centrifugation with deionized water at a centrifugal speed of 4000 rpm, and then vacuum dried at 110°C for 24 hours to obtain an iron-based Prussian blue positive electrode material, recorded as Gl-PBA.

[0058] Comparative Example 1 This comparative example provides a method for preparing an iron-based Prussian blue positive electrode material, comprising the following steps: Dissolve 5 mmol of FeSO4·7H2O and 1 mL of concentrated hydrochloric acid (mass concentration 36%) in 25 mL of deionized water and stir evenly to obtain a first solution; Dissolve 5 mmol of Na4Fe(CN)6 (mass 1.52 g) and 1.5 g of NaCl (25.67 mmol) in 25 mL of deionized water and stir well to obtain a second solution; 100 mL of deionized water was used as the third solution; Under stirring conditions at room temperature, the first solution and the second solution were simultaneously added to the third solution through a peristaltic pump at a speed of 1 mL / min, and the solution became a blue suspension after the addition was completed; stirring was continued for 5 hours, and finally aged at room temperature for 24 hours; after pouring out the supernatant, the obtained blue precipitate was centrifugally washed 3 times with deionized water at a centrifugal speed of 4000 rpm, and then vacuum dried at 110°C for 24 hours to obtain an iron-based Prussian blue positive electrode material.

[0059] Comparative Example 2 This comparative example provides a method for preparing an iron-based Prussian blue positive electrode material, comprising the following steps: Dissolve 5 mmol of FeSO4·7H2O and 1 mL of concentrated hydrochloric acid (mass concentration 36%) in 25 mL of deionized water and stir evenly to obtain a first solution; Dissolve 5 mmol of Na4Fe(CN)6 (mass 1.52 g) and 1.5 g of NaCl (25.67 mmol) in 25 mL of deionized water and stir well to obtain a second solution; 100 mL of 0.90 mol / L ethylene glycol-water solution was used as the third solution, wherein the molar concentration of hydroxyl group was 1.80 mol / L; Under stirring conditions at room temperature, the first solution and the second solution were simultaneously added to the third solution through a peristaltic pump at a speed of 1 mL / min, and the solution became a blue suspension after the addition was completed; stirring was continued for 5 hours, and finally aged at room temperature for 24 hours; after pouring out the supernatant, the obtained blue precipitate was centrifugally washed 3 times with deionized water at a centrifugal speed of 4000 rpm, and then vacuum dried at 120°C for 24 hours to obtain an iron-based Prussian blue positive electrode material.

[0060] Comparative Example 3 This comparative example provides a method for preparing an iron-based Prussian blue positive electrode material, comprising the following steps: Dissolve 5 mmol of FeSO4·7H2O and 1 mL of concentrated hydrochloric acid (mass concentration 36%) in 25 mL of deionized water and stir evenly to obtain a first solution; Dissolve 5 mmol of Na4Fe(CN)6 (mass 1.52 g) and 1.5 g of NaCl (25.67 mmol) in 25 mL of deionized water and stir well to obtain a second solution; 100 mL of 0.55 mol / L ethyl acetate-water solution was used as the third solution; Under stirring conditions at room temperature, the first solution and the second solution were simultaneously added to the third solution through a peristaltic pump at a speed of 1 mL / min, and the solution became a blue suspension after the addition was completed; stirring was continued for 5 hours, and finally aged at room temperature for 24 hours; after pouring out the supernatant, the obtained blue precipitate was centrifugally washed 3 times with deionized water at a centrifugal speed of 4000 rpm, and then vacuum dried at 120°C for 24 hours to obtain an iron-based Prussian blue positive electrode material.

[0061] The iron-based Prussian blue cathode material prepared in Example 1 was analyzed by X-ray powder diffractometer, using Cu-k as the radiation source, a wavelength of 1.5406, a Ni filter, a tube current of 40 mA, a tube voltage of 40 kV, a scanning range of 10-90°, a scanning speed of 8° / min, and a step length of 0.02°. The phase identification and crystal structure information were analyzed by JADE 6.0 software. The results are shown in FIG. Figure 1 shown.

[0062] Depend on Figure 1It can be seen that the EG-PBA of Example 1 has good crystallinity, and each diffraction peak is basically consistent with the standard card (JCPDS, NO.52-1907).

[0063] The microscopic morphology of the iron-based Prussian blue positive electrode materials prepared in Example 1 and Comparative Example 1 was observed using a scanning electron microscope of model S-4800 at an accelerating voltage of 20 kV. The results are shown in FIG. Figure 2 , Figure 3 shown.

[0064] Figure 2 is a SEM image of the iron-based Prussian blue positive electrode material of Example 1, Figure 2 It can be seen that the iron-based Prussian blue positive electrode material obtained in Example 1 exhibits a relatively regular cubic phase with a more regular morphology, and the particles are relatively dispersed and the particle agglomeration is relatively light, so that the interstitial water phase in the particles will be smaller, and the subsequent electrochemical performance will be more complete in sodium removal / sodium insertion.

[0065] Figure 3 The SEM image of the iron-based Prussian blue cathode material of Comparative Example 1 is shown in FIG. Figure 3 It can be seen that the iron-based Prussian blue positive electrode material obtained in Comparative Example 1 has a large particle size and serious agglomeration phenomenon. Sodium ions cannot be smoothly embedded / released, resulting in obstruction in the charging and discharging process during subsequent electrochemical performance tests, affecting the capacity of the positive electrode material.

[0066] Application Examples 1~2, Comparative Application Examples 1~3 The iron-based Prussian blue positive electrode material, conductive carbon black (Super P Li) and polyvinylidene fluoride (PVDF, molecular weight 1 million) of Examples 1-2 or Comparative Examples 1-3 were mixed in a mass ratio of 7:2:1, and a solvent N-methylpyrrolidone (NMP) was added to mix them into slurry; the mixed slurry was coated on aluminum foil respectively, and the coating amount of the iron-based Prussian blue positive electrode material on the aluminum foil was 2 mg / cm 2 ; After drying, cut into discs with a diameter of 10 mm as the positive electrode; A metal sodium sheet with a diameter of 10 mm was used as the negative electrode; Glass fiber (manufacturer Whatman, model GF / D, grade No. 1823-090) is the diaphragm; The electrolyte is prepared from NaClO4, EC (ethylene carbonate), DEC (diethyl carbonate) and FEC (fluoroethylene carbonate); the concentration of NaClO4 is 1.0 mol / L, the volume ratio of EC to DEC is 1:1, and the mass fraction of FEC in the electrolyte is 5%; The sodium ion battery was assembled in an argon glove box.

[0067] The sodium ion batteries assembled in Example 1~2 and Comparative Application Examples 1~3 were tested using a LAND battery tester, with a test voltage of 2.0~4.0V.

[0068] Figure 4 The sodium ion batteries of Application Examples 1-2 and Comparative Application Examples 1-3 are charged at a current of 10C (1C = 170 mAh g -1 ) The charge and discharge data of the first 500 cycles. Figure 4 It can be seen that the sodium ion batteries assembled in Application Examples 1 and 2 can provide 66.7 mAh g at a high rate of 10C. -1 and 61.1 mAh g -1 and after 500 cycles, they have a high capacity retention rate of 90.97% and 99.00%, respectively. In contrast, the sodium ion batteries assembled in Examples 1 to 3 can only provide 12.2 mAh·g at a high rate of 10C. -1 , 20.1mAh·g -1 and 40.2mAh·g -1 In addition, after 500 cycles, the coulombic efficiency of the sodium ion batteries assembled in Application Examples 1-2 and Comparative Application Examples 1-3 remained at about 99%, with no significant difference.

[0069] Figure 5 The rate performance diagram of the sodium ion battery assembled for application examples 1-2 and comparative application examples 1-3 at 0.1 / 0.2 / 0.5 / 1 / 2 / 5 / 10 / 0.1C (1C=170mAh·g -1 ).Depend on Figure 5 It can be seen that the batteries installed in application examples 1 and 2 have good rate performance and can provide 93.9 mAh g at a current of 5C. -1 and 82.0mAh·g -1 The specific capacity of -1 and 68.6 mAh g -1 The specific capacity of the battery was 97.95% and 96.81% after recovery to 0.1C. The batteries in comparative application examples 1 to 3 were significantly lower than those in application examples 1 to 2 at all rates. In addition, the coulombic efficiency of the batteries in application examples 1 to 2 and comparative application examples 1 and 3 was maintained at about 99% at different currents, while the coulombic efficiency of the batteries in comparative application example 2 was low, only about 80%.

[0070] Figure 6 The sodium ion battery of Application Example 1 is at a current of 0.1C (1C = 170mAh g -1 ) The charge and discharge curves of the first three cycles. Figure 6It can be seen that Application Example 1 has two platforms at 2.6V~3.0V and 3.3V~3.6V during both charging and discharging: during charging, the longer platform at 2.6V and the shorter platform above 3.3V correspond to the high-spin Fe 2+ and low-spin Fe 2+ oxidation, and the two discharge platforms correspond to the two Fe 3+ Reduction to Fe 2+ At the same time, due to the initial trivalent iron content of the Prussian blue structure, the first charge capacity is lower than the subsequent charge capacity. The first discharge capacity is 114.97 mAh g -1 .

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an iron-based Prussian blue positive electrode material, characterized in that: The following steps are involved: Mixing ferrous salt, acid and water to obtain a first solution; mixing a cyanide source, a sodium supplement and water to obtain a second solution; mixing the water-capturing agent with water to obtain a third solution; The first solution, the second solution and the third solution are mixed and aged to obtain an iron-based Prussian blue positive electrode material; The water-capturing agent is an acidic or neutral organic solvent having a functional group capable of forming hydrogen bonds and being miscible with water in any proportion; the functional group capable of forming hydrogen bonds should have both a hydrogen bond donor and a hydrogen bond acceptor.

2. The preparation method according to claim 1, characterized in that: The ferrous salt includes ferrous chloride or ferrous sulfate; In the first solution, the ratio of the molar amount of the ferrous salt to the volume of the water is 1 mmol: 3-7 mL.

3. The preparation method according to claim 1 or 2, characterized in that: The acid includes hydrochloric acid and / or acetic acid, and the mass concentration of the acid is 36-38%; In the first solution, the volume ratio of the acid to the water is 1:10-40.

4. The preparation method according to claim 3, characterized in that: The cyanide source includes sodium ferrocyanide; the sodium supplement includes one or more of sodium chloride, sodium acetate, and sodium oxalate; The molar ratio of the cyanide source to the sodium supplement is 1:2-8; In the second solution, the ratio of the molar amount of the cyanide source to the volume of the water is 1 mmol: 3-7 mL.

5. The preparation method according to claim 1, characterized in that: The water-capturing agent includes one or more of methanol, formic acid, formamide, ethanol, acetic acid, ethylene glycol, propanol, propionic acid, propylene glycol, glycerol, and isopropanol; The concentration of the functional groups capable of forming hydrogen bonds in the water-capping agent in the third solution is 0.92-1.28 mol / L.

6. The preparation method according to claim 1, characterized in that: The molar ratio of the ferrous salt to the cyanide source is 1:0.5-2; The volume ratio of water in the first solution to the third solution is 1:2-6.

7. The preparation method according to claim 1 or 6, characterized in that: The method of mixing the first solution, the second solution and the third solution is: simultaneously dropping the first solution and the second solution into the third solution to disperse; The rate at which the first solution is added dropwise to the third solution is independently 0.5 to 5 mL / min and the temperature of the addition is room temperature; The dispersion time is 2 to 8 hours.

8. The preparation method according to claim 1, characterized in that: The aging temperature is room temperature, and the aging time is 8 to 48 hours.

9. The iron-based Prussian blue positive electrode material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the iron-based Prussian blue positive electrode material according to claim 9 in sodium ion batteries.

Citation Information

Patent Citations

  • Prussian blue positive electrode material and preparation method and application thereof

    CN116598484A

  • Preparation method of Prussian blue material and application of Prussian blue material in sodium ion battery positive electrode material

    CN116605887A

  • Prussian blue analogue as well as preparation method and application thereof

    CN119018911A

  • Inert transition metal element doped iron-based Prussian blue sodium ion battery positive electrode material

    CN113104863A

  • Prussian blue sodium ion battery positive electrode material and preparation method thereof

    CN113488646A

Cited By

  • High-crystallinity prussian blue positive electrode material and preparation method thereof

    CN122464435A